186k views
1 vote
(3a^4b)(5ab^2)-(a^5b^2)(9b)

1 Answer

3 votes

Answer:

The expanded value of the given expression is


(3a^4b)(5ab^2)-(a^5b^2)(9b)=6a^5b^3

Explanation:

Given expression is


(3a^4b)(5ab^2)-(a^5b^2)(9b)

To find the value of the given expression:


(3a^4b)(5ab^2)-(a^5b^2)(9b)=15a^5b^3-9a^5b^3

(By multiplying the products and doing algebraci subtracion of the above expression)

Now taking the common terms in the above equation we get


(3a^4b)(5ab^2)-(a^5b^2)(9b)=3a^5b^3(5-3)


=3a^5b^3(2)


=6a^5b^3

Therefore the expanded value of the given expression is


(3a^4b)(5ab^2)-(a^5b^2)(9b)=6a^5b^3

User Maz
by
4.5k points